PENGARUH KOMPETENSI PROFESIONAL DAN KEDISIPLINAN TERHADAP KINERJA GURU SMP NEGERI DI KABUPATEN KUDUS DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MODERATOR (Students' Journal of Economic and Management, 2013)
This study aims to identify and examine the effect of Professional Competence, Discipline and Motivation on the Performance of State Yunior High School teachers in Kudus Sampling was done by using Simple Random Sampling Proportional. Of samples used in this study amounted to 229 people. Engineering test data used in this study include test validity with factor analysis the Kaiser-Meyer-Olkin (KMO), reliability tests with Cronbach alpha formula, Classical Assumption Test (Test Normality, Multicollinearity Test, Test Glejser) and Test Model Fit  The results showed that the professional competence has a positive and significant impact on teacher performance .. Discipline has a positive and significant impact on teacher performance. Motivation has a positive and significant impact on teacher performance. Keywords: Professional Competence, Discipline, Motivation and Performance teacher